2020
DOI: 10.3389/fpsyt.2020.577135
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Related Distress Is Associated With Alcohol Problems, Social Media and Food Addiction Symptoms: Insights From the Italian Experience During the Lockdown

Abstract: Background: Several scholars hypothesize that one of the most negative impacts of the coronavirus disease 2019 (COVID-19) crisis would concern the increase of prevalence and severity of both substances and behavioral addiction. Despite the general concerns about the increase of prevalence and severity of addictions related to the COVID-19 emergency, few data are still available. Thus, the main aim of this study was to investigate the association between COVID-19 related distress and: (i) alcohol problems, (ii)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
50
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 64 publications
(78 reference statements)
6
50
0
4
Order By: Relevance
“…Additionally, it was reported that 13% of the population that adhered to this diet increased their weight [ 28 ]. The psychological impact caused by this syndrome has been associated with symptoms of food dependence [ 43 ], that is, people are eating more, regardless of whether this diet is considered healthy, since it would be a way to alleviate the psychological discomfort created during this period. In this way, excess calorie intake can lead to an increase in BMI and harm people’s health [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was reported that 13% of the population that adhered to this diet increased their weight [ 28 ]. The psychological impact caused by this syndrome has been associated with symptoms of food dependence [ 43 ], that is, people are eating more, regardless of whether this diet is considered healthy, since it would be a way to alleviate the psychological discomfort created during this period. In this way, excess calorie intake can lead to an increase in BMI and harm people’s health [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Noteworthy, the alcoholic drinks were largely accessible during the lockdown, since supermarkets and liquor stores remained open, and delivering from on-line stores was always possible. On the other hand, bar and restaurants were shut down, thus significantly limiting the opportunities for “social drinking” ( 44 ). The cogency of hair EtG as a biomarker for monitoring and retrospective analysis of average alcohol consumption has been proved once again, particularly when large population datasets are available.…”
Section: Discussionmentioning
confidence: 99%
“…Italian citizens were not allowed to leave their homes; an exception was made for buying essential goods, special working demands and/or for urgent health reasons. Although such restrictive measures were necessary to contain the spread of the COVID-19 pandemic across the country, as suggested by major international public health agencies, an emerging body of scientific evidence highlights the detrimental effects of long-term quarantine on psychological health ( Panno et al, 2020 ; Rajkumar 2020 ; Yamada et al, 2021 ). Social distancing, self-isolation, and the associated stressors including fear, boredom and financial loss have produced long-lasting psychological effects, such as post-traumatic stress symptoms, confusion, anger, panic disorders, anxiety, and depression ( Brooks et al, 2020 ; Qiu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%